2016
DOI: 10.5539/jmbr.v6n1p71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mushroom (Coriolus versicolor) Based Probiotic on the Expression of Toll-like Receptors and Signal Transduction in Goat Neutrophils

Abstract: Neutrophils recognize and destroy pathogens through activation of the Toll like receptor (TLR) system as part of the inflammatory response of innate immunity. The expression and modulation of genes in the TLR signaling pathway in caprine blood neutrophils was investigated. Following initial screening for infection, goats (N=15) were assigned to three groups of five (n=5) individuals. Goats were drenched daily with 10 mL of powdered CorPet (Mycology labs Inc) soaked in hot (treatment I) or cold (treatment II) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In our study, probiotics had an effect in the expression of TLR3 and TLR8 in goats, and increase in expression of TLR4, TLR6, TLR7 and TLR9. Several studies have reported the effect of probiotics on TLR (AdjeiFremah et al, 2016b;Adjei-Fremah et al, 2017, Ekwemalor et al, 2016c, Tirumurugaan et al, 2010, Liu et al, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, probiotics had an effect in the expression of TLR3 and TLR8 in goats, and increase in expression of TLR4, TLR6, TLR7 and TLR9. Several studies have reported the effect of probiotics on TLR (AdjeiFremah et al, 2016b;Adjei-Fremah et al, 2017, Ekwemalor et al, 2016c, Tirumurugaan et al, 2010, Liu et al, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…CV is considered as an important medicinal agent due to its provision of essential nutrients and therapeutic applications, particularly regarding its apparent pharmacological properties of antitumor, immunomodulatory, cell reinforcement, antinociceptive, disease mitigative, antimicrobial, hepatoprotective and hypolipidemic activities, among others (5). A control cyclophosphamide group was used in the present study, as cyclophosphamide is frequently used as a chemotherapeutic for the treatment of cancer, due to its targeting of rapidly dividing cells (despite some interference with normal cell development) (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reported antiviral, hypocholesterolemic and hepatoprotective properties of mushrooms (4) is concurrent with the identification of seven partially-purified polysaccharides with cancer preventative and immunomodulatory activities in consumable and therapeutic mushroom species (Agaricus biosporus, Agaricus brasiliensis, Phellinus linteus, Ganoderma lucidum, Ganoderma applanatum, Lentinus edodes and Trametes versicolor), all of which contained glucose as the prevalent monosaccharide, among varying amounts of other α-glucans (3). Coriolus versicolor (CV) is among the established species of edible mushrooms (5). The significance of CV has been acknowledged regarding it high content of biological compounds including polysaccharides (starch, chitin), phenols (gallic, protocatechuic acid, catechin), steroids (ergosterol), vitamins (B1, B2, C and D) and minerals (calcium, selenium) (3).…”
Section: Introductionmentioning
confidence: 99%
“…These sites include the oral cavity, intestines, vagina and the skin [34]. In ruminants, probiotics are usually administered orally [35][36][37][38][39][40][41][42][43]. A study by Deng et al [44,45] utilized intravaginal infusion as mode of administering probiotics (containing a lactic acid bacteria mixture) to periparturient cows.…”
Section: Administration Of Probioticsmentioning
confidence: 99%